(untitled) (Conferencea, 2023)
The organization and reform of the educational process in accordance with modern requirements depends in many ways not only on the formation of pedagogical skills in future pedagogues, but also on the formation of the culture of educational management based on the management of the entire lesson process. The opportunities given to young people by our state lead them to increase their potential on a global scale, and this process requires reforms in modern education management. From this article, it is recommended to educate future pedagogues based on modern pedagogical approaches based on spiritual and moral values, and thereby use them in the formation of management culture.